2017
DOI: 10.1097/md.0000000000008969
|View full text |Cite
|
Sign up to set email alerts
|

A rare variation of celiac trunk and hepatic artery complicating pancreaticoduodenectomy

Abstract: Rationale:Anatomical variations of the celiac trunk and the hepatic artery are of considerable importance in hepatopancreatobiliary surgery, liver transplants, and radiological abdominal interventions.Patient concerns:Here, we report a 57-year-old man with 2 weeks of painless progressive jaundice. Preoperative imaging and cytology brush results suggested an ampullary tumor and common hepatic artery anomaly (CTA) was reported. The patient underwent pancreaticoduodenectomy (PD). Intraoperatively, the CHA and gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 22 publications
1
27
0
2
Order By: Relevance
“…This becomes complicated when there are variations in the hepato-biliary vasculature which usually originates from the celiac trunk. Ye et al (2017) recently reported a case in which they successfully performed pancreaticoduodenectomy in a cholangiocarcinoma patient without a classic celiac trunk. In this patient, the LGA and SA arose from the abdominal aorta and an accessory LHA arising from the LGA.…”
Section: Clinical Relevance Of the Celiac Trunk And Its Branchesmentioning
confidence: 99%
“…This becomes complicated when there are variations in the hepato-biliary vasculature which usually originates from the celiac trunk. Ye et al (2017) recently reported a case in which they successfully performed pancreaticoduodenectomy in a cholangiocarcinoma patient without a classic celiac trunk. In this patient, the LGA and SA arose from the abdominal aorta and an accessory LHA arising from the LGA.…”
Section: Clinical Relevance Of the Celiac Trunk And Its Branchesmentioning
confidence: 99%
“…The CT is normally 1.5 to 2.3 cm long, and its trunk traverses horizontally forward, trifurcating into the LGA, CHA, and SA (55-100% of the population) [1,3,4,[6][7][8][9][10]12,14,16,18,[23][24][25][26]28,29,33,34,[39][40][41][42][43][44]. This trifurcation was first described by Haller in 1756 as tripus Halleri [7,8,18,21,22,24,28,30,35,45,46]. The origin of the CT from the abdominal aorta, however, can vary.…”
Section: Celiac Trunk Variationsmentioning
confidence: 99%
“…Makisalo et al (1993) and Raviprasanna and Kulkarni (2018) reported one case in each of their cohorts that had an accessory LHA arising from the CT [45,56,57]. In its absence (0.38-1.4%), branches of the CT may arise from the aorta [4,7,8,27,28,34,35,38,[42][43][44]58].…”
Section: Embryonic Developmentmentioning
confidence: 99%
“…Some studies report the coexistence of Dunbar syndrome with pancreatic carcinoma [ [9] , [10] , [11] , [12] , [13] ] with present a surgical challenge during the resection of the pancreatic head. To our knowledge, silent PNETs was not reported in combination of Dunbar syndrome.…”
Section: Introductionmentioning
confidence: 99%